The Role of Isoinertial Training in Improving Lower Limbs Strength - H.A. Burileanu; R.V. Munteanu; A.R. Stepan; G.A. Cosma (Editura Universitatii Transilvania din Brasov, 2023)
The role of isoinertial training in improving lower limb strength is the aim of this study, because, although the place and the role of isoinertial training is still debated in specialized literature, in practice, it is gaining more and more consideration. Methods. We used the CMJ test from Optojump as a measurement method, and the intensive training was carried out over 12 weeks with Romanian sprinters (N=10). As a way of comparison, the test, and retest method was used. During the training, modern devices were used to monitor the training of Romanian sprinters, by introducing a device that acts mainly on eccentric strength. The data were processed using the SPSS program. Significant statistical differences were found in the value of the height of the vertical jump (CMJ), (Z= 3.51, p=0.00).